Dengue COVID-19 overlap: antigenic mimicry or concurrent two viral diseases (Bangladesh Journal of Medical Science, 2024)
Background: Dengue-COVID-19 overlap is mixture of both diseases sharing few similarities in pulmonary and extrapulmonary involvement. Due to high prevalence of both diseases later being pandemic disease, and overlapping laboratory and clinical parameters we have conducted a study to observe dengue-COVID-19 overlap in Indian settings in tertiary care hospitals.Methods: Prospective, observational study, included 600 COVID-19 cases with dengue NS1 or Dengue IgM positive, with lung involvement documented and categorized on HRCT thorax at entry point. All cases were subjected to dengue IgG antibody titers and dengue IgM/IgG antibody titer analysis after 12 weeks of discharge form hospital.Results: Dengue- COVID-19 overlap was documented in 16.33% (98/600) cases. CT severity has documented significant correlation with Dengue-COVID-19 overlap cases. [p